STATE AND DIGITAL VECTORS OF THE DEVELOPMENT OF THE MARKET OF INCLUSION OF UKRAINE - MAZUR, Dmytro; MAZUR, Oleksandr; МАЗУР, Галина; KOVBII, Antonina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the current state and digital vectors of the development of the insurance market of Ukraine and identifies promising directions for the digitalization of insurance.The essence of the insurance category is revealed. It is noted that the insurance market in Ukraine lags far behind developed countries. An analysis of the dynamics of the number of participants in the insurance market, the amount of assets of insurance companies, the structure of the insurance portfolio by types of insurance was carried out, and the main trends of the insurance market in Ukraine were revealed. The keys to the stable development of insurance activity in Ukraine have been defined as: quick response to new conditions and customer requests; the ability to adapt, accumulate positive experience, analyze and correct negative moments; develop harmoniously, find a balance between the accumulation of new knowledge and their practical application.Factors influencing and functioning of the domestic insurance market are determined.The features of modern trends in digital insurance tools, as an important mechanism for the growth of the insurance market, are revealed.It was found InsurTech  that modern technologies are important for insurance companies. These  InsurTech nclude artificial intelligence technologies, new inventions in the field of cyber security, big data analysis («bigdata), blockchain technologies, the Internet of Things (LoT ) and smartphone applications.
Keywords: страхування; страховий ринок; цифровізація; цифрові інструменти; іншуртех; bigdata; штучний інтелект; Інтернет речей